Asymptomatic Plasmodium Infections in Children in Low Malaria Transmission Setting, Southwestern Uganda - Roh, Michelle E.; Oyet, Caesar; Orikiriza, Patrick; Wade, Martina; Kiwanuka, Gertrude N.; Mwanga-Amumpaire, Juliet; Parikh, Sunil; II, Yap Boum (Emerging infectious diseases, 2016)
Asurvey of asymptomatic children in Uganda showed Plasmodium malariae and P. falciparum parasites in 45% and 55% of microscopy-positive samples, respectively. Although 36% of microscopy-positive samples were negative by rapid diagnostic test, 75% showed P. malariae or P. ovale parasites by PCR, indicating that routine diagnostic testing misses many non–P. falciparum malarial infections.
Keywords: Plasmodium Infections; Malaria Transmission; Children; Uganda; Survey